2008
DOI: 10.5483/bmbrep.2008.41.10.716
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic EBP2 expression enhances cyclin E1 expression and induces chromosome instability in HEK293 stable clones

Abstract: To explore the effects of deregulated expression of the EBNA1 binding protein 2 (EBP2) on cell growth, we generated human HEK293 stable clones constitutively expressing an EBP2-EGFP fusion protein. We found both RNA and protein levels of cyclin E1, a dominant oncoprotein, were elevated in the EBP2-EGFP stable clones. These findings were confirmed by flow cytometry bivariate analysis of cyclin expression versus DNA content. Moreover, the increase in p21 expression and the specific phosphorylation at Ser1981 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although previous study indicates that overexpression of EBP2 can promote the cell proliferation of HEK293 cells, 21 its role in the tumorigenesis is still unclear. In our study, we identified that EBP2 is upregulated in lung cancer cells and tissues.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although previous study indicates that overexpression of EBP2 can promote the cell proliferation of HEK293 cells, 21 its role in the tumorigenesis is still unclear. In our study, we identified that EBP2 is upregulated in lung cancer cells and tissues.…”
Section: Discussionmentioning
confidence: 96%
“…20 Overexpression of EBP2 has been shown to be able to promote the cell proliferation and chromosome instability of 293 cells or NIH3T3 cells. 21, 22 A recent study demonstrates that EBP2 is essential for the nucleolar localization of Fbw7γ via direction interaction. 23 However, the biological functions of mammal EBP2, such as whether it may affect the stability of Fbw7 γ substrates, remain not completely understood.…”
mentioning
confidence: 99%
“…of cyclin E1 and subsequent chromosome instability (26,33). Whether EBNA-1 modulates such aspect of EBP2 functions during interphase merits a careful examination.…”
Section: Discussionmentioning
confidence: 99%
“…Karyotype analysis of 293_CHI3L1 clones have shown that these cells differ from wild type [31,32] and control cells (293_pcDNA3.1) in modal chromosome number and structure of chromosomes (manuscript in preparation). Other authors have also shown that overexpression, for example, of tripeptidyl-peptidase II [33], EBNA1 binding protein 2 [34], GLI1 transcripton factor [35] or Cut homeobox 1 trancription factor [36] have triggered centrosome and chromosomal abnormalities in 293 cells.…”
Section: Immortalization and Transformation: The Central Role Of Karymentioning
confidence: 99%